2011
DOI: 10.1126/scitranslmed.3002613
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Vulvovaginal Fungal Infections Cause Persistent Pain in a Mouse Model of Vulvodynia

Abstract: Provoked vestibulodynia, the most common form of vulvodynia (unexplained pain of the vulva), is a prevalent, idiopathic pain disorder associated with a history of recurrent candidiasis (yeast infections). It is characterized by vulvar allodynia (painful hypersensitivity to touch) and hyperinnervation. We tested whether repeated, localized exposure of the vulva to a common fungal pathogen can lead to the development of chronic pain. A subset of female mice subjected to recurrent Candida albicans infection devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
117
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 35 publications
11
117
1
Order By: Relevance
“…The EvF protocol can easily be modified for use on tissues other than the hind paw e.g. abdomen 7 and ano-genital ridge 8 where CvF is currently used. Rodent models of allergies, wound healing, neuropathies and other pathologies can be easily adapted to include measures of mechanical sensitivity in tissues including and beyond the hind paw.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EvF protocol can easily be modified for use on tissues other than the hind paw e.g. abdomen 7 and ano-genital ridge 8 where CvF is currently used. Rodent models of allergies, wound healing, neuropathies and other pathologies can be easily adapted to include measures of mechanical sensitivity in tissues including and beyond the hind paw.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in time and intensity of previously specified responses to noxious stimuli are used to measure pain states in these animals as rodent subjects are not otherwise able to report a sensation of pain 6 . Altered responses to temperature and pressure are commonly used as metrics of tissue sensitivity in rodent models of inflammatory nociception that can be caused by infection 7,8 , chemical exposure 6,9,10 , surgical incision 11 , as well as neuropathic pain caused by nerve ligation 12 …”
Section: Introductionmentioning
confidence: 99%
“…Error bars represent the SEM. Farmer et al, 2011) and involves different inflammatory components such as infiltration and degranulation of mast cells (Toyoda et al, 1994), neurogenic inflammation (Nakamura et al, 2003), plasma extravasation (Otten et al, 1984), and increased levels of proinflammatory cytokines (Darsow et al, 1997;Nakamura et al, 2003). The above changes are known to induce a substantial increase in NGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it has also been postulated that an inability to clear vulvovaginal infections and the resulting inflammation may lead to the development of vulvodynia. Although the literature contains inconsistent histopathological findings [43,46,44,47], the former point is supported by an experimental mouse model of vulvodynia that confirmed that repeated vulvovaginal infections with Candida albicans led to chronic vulvar pain behavior and increased vulvar innervation [48]. Finally, vulvodynia may be associated with some degree of pelvic floor muscle dysfunction.…”
Section: Biomedical Factorsmentioning
confidence: 99%